Controlled Synthesis of Small Water-Soluble Hybrid Gold Nanoparticles: An Optimized Strategy for Stable Nano-Dispersion and Towards Cellular Uptake - Bouyon Yenda, Tracy; Jiguet-Jiglaire, Carine; Khichane, Imene; Gobert, Quentin; Prabhakaran, Rathinasabapathi; De Nonneville, Alexandre; Djenizian, Thierry; Salas, Sébastien; Dallemer, Frédéric (Frontiers in Mechanical Engineering, 2022)
The development of effective drug delivery systems is one of the major challenges in the fight against cancer. Gold nanoparticles could effectively harness cancer therapies by improving their potency while reducing toxic side effects. In this work, we describe a high-yield one-step synthesis of small water-soluble gold nanoparticles (AuNPs). Efficient purification was monitored, and discrete structure was fully characterized by combining molecular analytical technics (UV-visible and NMR spectroscopies) and solid-state analyses (thermal gravimetric analysis and transmission electron microscopy). These AuNPs have good dispersibility in various biocompatible media and can be used without any additives. Preliminary study with in vitro treatment of IB115 human cancer cells showed massive cellular uptake associated to moderate intrinsic cytotoxicity. The high control of the synthesis and the small size of these AuNPs are offering fine surface properties control, crucial for challenging biological nano-dispersion issues. Thus, limitation of the agglomeration of nanoparticles and improvement of interaction with the surface of cell should open new leads for vectorization of drugs or imaging probes for diagnosis.